2019
DOI: 10.1016/j.cmet.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Metabolism Regulates Proliferation and Lineage Allocation in Skeletal Stem Cells

Abstract: Graphical AbstractHighlights d Skeletal stem cells increase glutamine metabolism during osteoblast differentiation d Glutamine metabolism regulates osteoblast and adipocyte specification d Mice unable to metabolize glutamine have less bone and increased marrow fat d Amino acid transaminase-derived a-ketoglutarate is critical for SSC proliferation SUMMARY Skeletal stem cells (SSCs) are postulated to provide a continuous supply of osteoblasts throughout life. However, under certain conditions, the SSC population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
176
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(188 citation statements)
references
References 71 publications
(69 reference statements)
4
176
0
Order By: Relevance
“…Loss of GLS specifically in mouse skeletal stem cells reduced the amount of osteoblasts [141]. Glutaminase and transaminase-dependent glutamate conversion to a-ketoglutarate were found to be required in mouse skeletal stem cells to proliferate and differentiate into osteoblasts [141]. Thus, glutamine consumption increases in proliferating, differentiated cells and in activated, proliferating skeletal stem cells.…”
Section: Amino Acid Metabolismmentioning
confidence: 98%
See 1 more Smart Citation
“…Loss of GLS specifically in mouse skeletal stem cells reduced the amount of osteoblasts [141]. Glutaminase and transaminase-dependent glutamate conversion to a-ketoglutarate were found to be required in mouse skeletal stem cells to proliferate and differentiate into osteoblasts [141]. Thus, glutamine consumption increases in proliferating, differentiated cells and in activated, proliferating skeletal stem cells.…”
Section: Amino Acid Metabolismmentioning
confidence: 98%
“…The enzyme glutaminase (GLS) deaminates glutamine to form glutamine as the first step in glutamine catabolism. Loss of GLS specifically in mouse skeletal stem cells reduced the amount of osteoblasts [141]. Glutaminase and transaminase-dependent glutamate conversion to a-ketoglutarate were found to be required in mouse skeletal stem cells to proliferate and differentiate into osteoblasts [141].…”
Section: Amino Acid Metabolismmentioning
confidence: 98%
“…In turn, glutamine metabolism provides carbon for lipids and glutathione biosynthesis and nitrogen for nucleotide biosynthesis and thus regulates oxidative stress and promotes tumor proliferation (Wise and Thompson, 2010;Le et al, 2012). Proliferation of skeletal stem cells can be regulated through glutamine metabolism (Yu et al, 2019), and the proliferation of intestinal stem cells can be regulated by mitochondrial pyruvate metabolism (Schell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In immune system, miRNA expression patterns can be used as a biomarker for particular disease states such as cancer or endocrine events. [27,28] Evidence also reported that exosomes can be taken up into neighboring or distant cell types to modulate the function of recipient cells. [29] Therefore, to explore the relationship between macrophage-derived exosomal miRNAs and BMSCs, we co-cultured these two cell types, revealing that exosomal miRNAs from macrophages could be internalized by BMSCs, providing a strong basis for our further research.…”
Section: M2d-exos-derived Mir-5106 Accelerates Fracture Healing In Vivomentioning
confidence: 99%